Case Report: Pathologic complete response in triple negative breast cancer treated with anthracycline free regimen - Piazza, Francesca; Scartabellati, Giulia; Moretti, Laura; Laganà, Marta; Vassalli, Lucia; Trevisan, Benedetta; Bazzoli, Michela; Schivardi, Greta; Canzi, Federico; Baraziol, Roberto; Ippolito, Giuseppe; Grisanti, Salvatore; et al. (Frontiers in Oncology, 2026)
Triple-negative breast cancer (TNBC) is a highly aggressive malignancy with limited therapeutic options and elevated mortality rates. Chemo-immunotherapy according to the KEYNOTE-522 has established a new standard of care in the neoadjuvant setting, due to high rates of pathological complete response (pCR) and improved survival outcomes. Recent evidence suggests the feasibility of treatment de-escalation, particularly the omission of anthracyclines, to mitigate treatment-related toxicity; however, this approach is yet to be established in clinical practice. We report the clinical case of a complete pathological response despite the omission of anthracyclines in a patient with high-risk TNBC. A 54-year-old Caucasian woman was diagnosed in February 2024 with cT4a cN0 TNBC and started neoadjuvant treatment according to the KEYNOTE-522 regimen. Radiologic mid-treatment evaluation showed a marked reduction in tumor size (22 mm vs 78 mm), supporting continuation to the second treatment phase. However, epirubicin extravasation required interruption of treatment, and prompt management of the risk of infection and necrosis was necessary. Once the risk of sepsis was ruled out, the patient underwent surgery, achieving pCR (ypT0, ypN0). This case supports the potential role of de-escalated regimen in selected patients and raises the hypothesis-generating question of whether the inflammatory response triggered by the extravasation of epirubicin has enhanced the immune-mediated anti-tumor effect, potentially making pembrolizumab more effective. The lack of validate predictive biomarkers for patient selection and the absence of reliable imaging techniques to predict pathologic complete response are also discussed. Tumor-infiltrating lymphocytes (TILs) are currently the only biomarkers consistently shown to predict response to neoadjuvant treatment; however, the low TIL level observed in our patient (5%) highlights that this parameter is still far from being a reliable tool to guide treatment de-escalation in clinical practice. Further investigation is warranted to identify which patients could safely benefit from reduced-intensity approaches without compromising outcomes and how clinicians can be guided in this decision-making process.